Actividades rurales y el agroturismo en la Parroquia Febres Cordero, Mata de Cacao - Lucio Samaniego, Dagmar Lourdes (2020)
The city of Babahoyo, land of great stories that promise a versatile city that is growing agro-tourism, converting agricultural and livestock activities as its main source of income for its inhabitants. Febres Cordero is a rural parish in the Babahoyo canton of the Los Ríos province in Ecuador. Created in the Las Juntas enclosure on May 14, 1936. Its inhabitants are dedicated to commerce, agriculture, livestock and tourism. It is one of the most important sectors for agriculture that is dedicated primarily to rural activities such as the production of cocoa, rice, corn, soybeans, bananas, etc. Its parish head is the town of Mata de Cacao, being one of the most extensive enclosures in inhabitants and territory of the parish, the same one that is beginning to grow thanks to its tourist activities, benefiting from a good economy. Tourism is one of the most booming activities in recent years, even in certain countries it has been considered one of the main sources of economic income, which is why some cities in the country work primarily to promote tourism because it is an activity that Great opportunities for growth and urban-rural development emerge for the future. Due to these characteristics, Babahoyo cannot be the exception, tourism and agrotourism must be promoted in its parishes.